2010
DOI: 10.1007/s00421-010-1641-1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of haematological parameters in athletes

Abstract: The influence of training and competition workloads is crucial for evaluation of longitudinal haematological data in athletes. There are only a few papers on the variation of haematological parameters during long-lasting periods and, especially, during an entire competitive season. We summarized that some haematological parameters can be influenced by long-term training and competition periods. Haemoglobin (Hb) and haematocrit (Ht) are decreased during the more intense periods of training, throughout the seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 34 publications
4
36
0
3
Order By: Relevance
“…However in the CG, these values remained close to baseline, with a tendency to decrease them. The decrease in these hematological parameters found in the CG was similar to that found in recent studies, in which authors measured decrease in hematological variables during the season when the training intensity and volume was higher (1). In contrast, during transition and no-training periods in professional cyclists, the opposite tendency was observed (19).…”
Section: Discussionsupporting
confidence: 67%
“…However in the CG, these values remained close to baseline, with a tendency to decrease them. The decrease in these hematological parameters found in the CG was similar to that found in recent studies, in which authors measured decrease in hematological variables during the season when the training intensity and volume was higher (1). In contrast, during transition and no-training periods in professional cyclists, the opposite tendency was observed (19).…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, activation of angiogenesis was suggested by the rise in vascular endothelial growth factor (VEGF) and hepatocyte growth factor (HGF) supporting a possible role of tissue hypoxia in modulating the response (Grochot-Przeczek et al, 2013). Although, several hematological parameters were increased after acute exercise it was reported that long-term training and competition periods such as 3-week professional competition (Giro d'Italia stage race) resulted in lower values of hemoglobin, red blood cells and hematocrit than baseline (Banfi et al, 2011;Corsetti et al, 2012). Thiol redox cycles play central roles in maintaining the redox state in cells.…”
Section: Discussionmentioning
confidence: 97%
“…Essa posição é corroborada por Karakoc et al 12 , que verificaram em jogadores de futebol, após 90 minutos de treinamento realizado dois dias após o jogo, uma diminuição da viscosidade sanguínea e subsequente reduções nos valores de Hb, VGM. No entanto, há de se destacar que o controle do peso e da hidratação dos atletas decorrer das 24, 48 e 72 horas, pode ser um fator limitante nesse processo.…”
Section: Discussionunclassified